URGENSI PENDIDIKAN ASWAJA DALAM MEMBENTUK KARAKTER PEMIMPIN ORGANISASI MAHASISWA - Widi Sis Ardiyanto; Darnoto Darnoto (Tarbiyatuna Kajian Pendidikan Islam, 2024)
UNISNU Jepara students are at the forefront in actualizing and implementing the value principles of aswaja. So the urgency of implementing the principles of aswaja values will become the provision and basis for UNISNU Jepara students, especially organizational leaders. The aim of the study is to determine the urgency of applying the principles of Aswaja values to student organization leaders at UNISNU Jepara so that these principles can bring out the inherent Aswaja character attitudes. The method used uses a qualitative method with a literature study approach sourced from journals, books and other reliable literature sources. The results of the research will illustrate that the urgency of the Aswaja character will be an important provision for every student in implementing the values of the principles of Aswaja such as being fair (Al-adl), tolerant (At-tasamuh), balanced (At-Tawasuth), as well as preventing bad things and calling for good thing (Amar ma'ruf nahi mungkar). This is the character that must be instilled in every organizational leader at UNISNU Jepara, besides that the teachings are used as a basis for running the organization, the aswaja character is also expected to be a style of leadership character that is firm, straightforward and dynamic in facing and resolving every challenge without ignoring the teachings of the Shari'a. Islam, the Aswaja character can be the basis for every leader of a student organization to have good morals, morals and character and can guide members in running and determining the direction of the organization. For this reason, the importance of instilling Aswaja values is needed as a tool to shape the character of student organization leaders at UNISNU Jepara.